Curve Fitting With Bootstrap Error Analysis And Its Application On Two-Dimensional Data - Sahubar Ali, Nur Soffiah (2019)
In data fitting, researchers use various methods to determine the quality of a fitting. Visualization of images is crucial in observing the behavior of data obtained. The problem in judging the accuracy of a result obtained through visual observation are commonly faced by researchers when handling contaminated data such as noisy data, missing data and outliers. In this research, study has been conducted to deal with those noisy data and missing data using least square titting (LSF).